Analysis of specialized terminology in the area of ​​conservation-restoration of cultural assets - José Antonio Pérez Botta (Perspectivas Metodológicas​)
Here is presented an advance of the investigation aimed at substantiating the need for standardization of the terminology of the area and conservation-restoration based on a detailed analysis of the theoretical terms used in the specialized bibliography recovered in scientific databases in 4 languages: Spanish of Latin American origin and of Iberian origin, Italian, French and English; It also includes surveys carried out on professionals in the discipline. An approach to the object of study was carried out from an integrated and shared theory with the same methodological design, bringing together quantitative scientific research with the principles of quality management and the conceptual matrix of the existence and conservation-restoration of cultural assets. It includes the epistemic-methodological framework used for the quantitative semantic analysis of the documents written in the native language of the authors. The terminological study was carried out through a mathematical modeling adopting a systemic perspective that provides an area of ​​convergence, complementation and articulation of the different interacting disciplinary domains in order to reach an agreement regarding the standardization of terminology and practical fact. that it represents.